RESIDUAL PLATELET REACTIVITY DURING THERAPY WITH INHIBITORS OF CYCLOOXIGENASE OR ADENOSINE DIPHOSPHATE RECEPTORS - A. A. Lomonosova; N. A. Mazur; E. A. Zolozova; E. V. Sayutina; V. V. Chigineva; N. V. Shestakova (Столичная издательская компания, 2015)
Aim. To compare effects of acetylsalicylic acid (ASA) and two clopidogrel drugs on residual platelet aggregative reactivity (RPAR). Material and methods. Patients (n=40) with ischemic heart disease aged under 70 years were involved into the crossover study. Clinical examination included questionnaire survey , blood pressure (BP) measurement, ECG registration, 24-hour ECG and BP monitoring, determination of blood levels of total cholesterol, high density lipoproteins, triglycerides, transaminases, and creatinine, complete blood cell count, including platelets number and hemoglobin level. Besides evaluation of the platelet aggregation by optical aggregometry was performed initially , after one week ASA treatment and after every next 3 week clopidogrel treatment period.  Results. RPAR during ASA monotherapy was 56.4±0.3%. There were no significant differences in effects of original and generic clopidogrel on RPAR. Сlopidogrel therapy reduced RPAR more significantly (42.2±0.2%) than ASA monotherapy did (p=0.0003). Authors proposed definition for high level of RPAR during therapy - it is platelet aggregation more than 46%. Data analysis taking into account this criterion showed that a number of patients with high RPAR was 70 and 30% among patients treated with enterosoluble ASA and clopidogrel, respectively. Conclusion. Study results show that a significant number of patients receiving antiplatelet monotherapy does not achieve the target level of RPAR(<46%). These results may be a rationale for combined therapy in patients of this type.